The world educational crisis : a systems analysis - Coombs, Philip H. (London ; New York : Oxford University Press, 1968)
It assembled in one place the root facts about world crises in education,tendencies inherent in them and strategies of dealing with them. It comprise of seven chapters: "Angle of Vision," "The Inputs of Educational Systems," "The Outputs of Educational Systems," "Inside the Educational System," "Non formal Education," "International Co-operation," and "Conclusions for Strategy(3y(B.s
Includes bibliographical references and index.
kjo 18/01/2019
Loans
Keywords: Education